It is equal to 6 when simplified
4x2 + 6x - 3 (with no remainder)
It is equivalent to: 6x^2 -24x
5x+15 = 6x-10 5x-6x = -10-15 -x = -25 x = 25
x=10
6x(1+4)
It is equivalent to 24x+44
It is: 4(6x+x) = 24x+4x => 28x
6x(3x2 - x + 4)
4(x2 - 6x + 13)
3x3-18x2+24x=3x(x2-6x+8)=3x(x-4)(x-2)
7+10+(-6x)=17-6x
24x^3 + 72x2 + 30x = 6x*(4x^2 + 12x + 5)=6x*(2x + 1)*(2x + 5)
30x2+25x-24x-20 = 30x2+x-20 = (6x+5)(5x-4) when factored
The GCF of 24x and 30x is 6x.
An example of how to use the distributive property: If you have 6x(5+4) you multiply 6x by 5 and get 30x. Then you multiply 6x by 4 and get 24x and then you would have 30x+24x which = 54x
It is equivalent to: 6x^2 -24x